Σ‐Silane Platinum(II) Complexes as Intermediates in C−Si Bond‐Coupling Processes. Issue 48 (5th August 2019) - Ríos, Pablo; Fouilloux, Hugo; Díez, Josefina; Vidossich, Pietro; Lledós, Agustí; Conejero, Salvador
Abstract: Platinum complexes [Pt(NHC′)(NHC)][BAr F ] (in which NHC′ denotes a cyclometalated N‐heterocyclic carbene ligand, NHC) react with primary silanes RSiH3 to afford the cyclometalated platinum(II) silyl complexes [Pt(NHC‐SiHR′)(NHC)][BAr F ] through a process that involves the formation of C−Si and Pt−Si bonds with concomitant extrusion of H2 . Low‐temperature NMR studies indicate that the process proceeds through initial formation of the σ‐SiH complexes [Pt(NHC′)(NHC)(HSiH2 R)][BAr F ], which are stable at temperatures below −10 °C. At higher temperatures, activation of one Si−H bond followed by a C−Si coupling reaction generates an agostic SiH platinum hydride derivative [Pt(H)(NHC′‐SiH2 R)(NHC)][BAr F ], which undergoes a second Si−H bond activation to afford the final products. Computational modeling of the reaction mechanism indicates that the stereochemistry of the silyl/hydride ligands after the first Si−H bond cleavage dictates the nature of the products, favoring the formation of a C−Si bond over a C−H bond, in contrast to previous results obtained for tertiary silanes. Furthermore, the process involves a trans ‐to‐ cis isomerization of the NHC ligand before the second Si−H bond cleavage. Abstract : Intermediacy of σ‐SiH Pt II complexes : Primary silanes are shown to form σ‐SiH complexes with cationic electron‐deficient Pt II complexes, [Pt(NHC′)(NHC)] + (see graphic). These compounds evolve at room temperature through a double Si−H bond activation process that involves the formation of C−Si and Si−Pt bonds with concomitant extrusion of H2 . Localized orbital analysis has revealed enhanced silylium character of the silicon atom when the silyl fragment is located at the apical position, which presumably favors the C−Si coupling event.